Vpliv vlažnosti na mikrotrdoto smrekovine, določeno z vtiskanjem - Žigon, Jure (Les (Ljubljana), 2023)
Hardness is a measure of the resistance of wood against the penetration of a harder body into its interior and often defines the usefulness of the selected type of wood for a particular purpose. In addition to density, the hardness of individual wood species is highly dependent on the moisture content of the wood. This study determined the hardness of Norway spruce wood conditioned at different relative humidities. Hardness measurements were performed by indenting a ball in radial wood surfaces on an instrument for determining the micromechanical properties of materials. The results showed that the hardness of wood decreases with increasing moisture content; the indentation hardness (HIT) and indentation elastic modulus (EIT) were 110.8±11.7 MPa and 0.62±0.01 GPa for absolutely dry wood, and for wood with a fibre saturation point of 29.4% they were 36.3±7.9 MPa and 0.40±0.05 GPa, respectively. The decrease in hardness of the wood with increasing moisture content was reflected in an increase in the depth of the indentations caused, and an increase in the surface roughness of the samples. Analysis of the wood tissue with a scanning electron microscope showed the flattening of the cell walls of the wood in the areas with indentations, their kneading into tracheid lumina, and the formation of cracks in the cell walls.
Keywords: hardness; indentation; les; micromechanical properties; mikromehanske lastnosti; scanning electron microscope; trdota; vlažnost lesa; vrstični elektronski mikroskop; vtiskanje; wood; wood moisture content